2015
DOI: 10.1007/s11420-015-9459-3
|View full text |Cite
|
Sign up to set email alerts
|

Useful Functional Outcome Can Be Achieved After Motor Nerve Transfers in Management of the Paralytic Hand. An Observational Study

Abstract: Background: Nerve transfers have demonstrated encouraging outcomes in peripheral nerve reconstructions compared with the conventional direct repair or grafting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 20 publications
(32 reference statements)
2
8
0
Order By: Relevance
“…12 Similarly, in their cohort of 55 patients who underwent nerve transfers for isolated injuries of radial, ulnar, and median nerves, Sallam et al found a downward trend in motor grade with increased BMI. 13 Consistent with Lee et al, they speculated that the poor fitness of patients with higher BMIs was a likely explanation for these findings. 12,13 Socolovsky et al published an interesting series of papers exploring the impact of BMI on nerve transfer outcomes.…”
Section: Impact Of Body Mass Index On Nerve Regeneration and Nerve Transfer Outcomessupporting
confidence: 67%
See 2 more Smart Citations
“…12 Similarly, in their cohort of 55 patients who underwent nerve transfers for isolated injuries of radial, ulnar, and median nerves, Sallam et al found a downward trend in motor grade with increased BMI. 13 Consistent with Lee et al, they speculated that the poor fitness of patients with higher BMIs was a likely explanation for these findings. 12,13 Socolovsky et al published an interesting series of papers exploring the impact of BMI on nerve transfer outcomes.…”
Section: Impact Of Body Mass Index On Nerve Regeneration and Nerve Transfer Outcomessupporting
confidence: 67%
“…13 Consistent with Lee et al, they speculated that the poor fitness of patients with higher BMIs was a likely explanation for these findings. 12,13 Socolovsky et al published an interesting series of papers exploring the impact of BMI on nerve transfer outcomes. 14,15 In their initial study, Socolovsky et al demonstrated that elevated BMI negatively impacted recovery of shoulder abduction in 18 patients who received spinal accessory to suprascapular nerve transfer for shoulder reanimation in brachial plexus injuries.…”
Section: Impact Of Body Mass Index On Nerve Regeneration and Nerve Transfer Outcomessupporting
confidence: 67%
See 1 more Smart Citation
“…21,22 Functional motor recovery was considered useful when a grade of M3 or more was achieved, and functional sensory recovery was considered useful when a grade of S3 or more was regained. 23,24 The Tinel sign and 2-point discrimination were used to evaluate the progress of nerve regeneration at 6 and 12 weeks after surgery and at 3-month intervals thereafter. Operative time for the microsuture group was the time required for the placement of 6 epineurial sutures; while for the fibrin glue group, it was the time necessary for sealant application, plus a standard setting time of 5 minutes.…”
Section: Outcome Measuresmentioning
confidence: 99%
“…The concept of nerve transfer for functional loss due to peripheral nerve injury has been described in the upper extremity. 15,33,34,38 Various anatomical feasibility studies, similarly, supported the use of a single nerve transfer technique for the treatment of neurologic foot drop. 1,9,29 Tibial nerve branches to the lateral head of the gastrocnemius, 23,25 soleus, 3,8,10,25 or flexor hallucis longus (FHL) and flexor digitorum longus (FDL) muscles 14 were previously investigated as possible donors to neurotize the injured deep peroneal nerve.…”
mentioning
confidence: 92%